Improving the means and methods of training of young fencers aged 9-11 years - Kriventsova, I.; Gorbachuk, Y.; Chernigivs`ka, S.; Jagiello, M.; Bensbaa, A. (Pedagogy of Physical Culture and Sports, 2021)
Background and Study Aim. Training of motor actions of young athletes requires consideration the peculiarities of the sensitive period of their development. An important component of the training program is the use of training tools that do not harm the health of young athletes. The purpose of the study is to identify the dynamics of physical training and provide an assessment of technical and tactical techniques of fencers (sword) aged 9-11 years under the influence of the author's program. Material and methods. The study involved young fencers (n = 20; age 9-11 years). The study lasted one academic year. The training was held in the gym of the children's and youth sports school "Wave" (Kharkiv, Ukraine). Athletes were divided into two uniform groups: control group (n = 10) and experimental group (n = 10). Classes were held according to the author's program 4 times a week for 2 hours. A survey of trainers of trainers (n = 12) and experienced fencers (n = 30) was conducted. Parents of children agreed to participate in the study. The following tests were used: "Standing Long Jump Test (Broad Jump), cm"; "4x9 m Shuttle test, sec."; "Hits into the target, 30 sec. points"; "Simulation exercises of a simple fencing combination, sec.". The program "Microsoft Excel" Data Analysis, SPSS was used. The level of reliability is selected p <0.05. Results. Significant changes in the indicators of the control group were obtained: "Standing Long Jump Test (Broad Jump), cm", (p <0.05); in the test "4x9 m Shuttle test, sec." (p <0.05); both tests have assessment of technical and tactical techniques (p <0.01). In the experimental group, all tests showed positive changes (p <0.01). In comparison of two groups with each other in the tests "Standing Long Jump Test (Broad Jump), cm", "4x9 m Shuttle test, sec." and " Hits into the target, 30 sec. points" there were positive statistically significant changes (p <0.05). In the test "Simulation exercises of a simple fencing combination, sec." no significant changes occurred (p?0.05). Conclusions. It is recommended to take into account the effects of exercise on the health of young athletes when designing a fencing training program.